2005
DOI: 10.1007/s10804-005-7030-z
|View full text |Cite
|
Sign up to set email alerts
|

EEG Biofeedback for Addictive Disorders—The State of the Art in 2004

Abstract: This paper reviews studies of brainwave biofeedback as a therapeutic technique for substance use disorder. This modality is attractive as a medication free, neurophysiologic, and self actualizing treatment for a substance based, brain impaired and self-defeating disorder. Three approaches are described and the literature for each reviewed. Alpha-theta occipital feedback was originally employed to facilitate autosuggestion in hypnagogic states to augment standard therapy approaches in substance abuse treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…A critical analysis of the Peniston Protocol is discussed at length in the previous reviews (Trudeau, 2000(Trudeau, , 2005a(Trudeau, , 2005b). Several controlled studies of the Peniston protocol for addictions, completed by Lowe (1999), Moore and Trudeau (1998), and Taub and Rosenfeld (1994), suggest that alpha-theta training for addictions may be nonspecific in terms of effect when compared to suggestion, sham or controlled treatment, or meditational techniques.…”
Section: Journal Of Neurotherapymentioning
confidence: 99%
See 4 more Smart Citations
“…A critical analysis of the Peniston Protocol is discussed at length in the previous reviews (Trudeau, 2000(Trudeau, , 2005a(Trudeau, , 2005b). Several controlled studies of the Peniston protocol for addictions, completed by Lowe (1999), Moore and Trudeau (1998), and Taub and Rosenfeld (1994), suggest that alpha-theta training for addictions may be nonspecific in terms of effect when compared to suggestion, sham or controlled treatment, or meditational techniques.…”
Section: Journal Of Neurotherapymentioning
confidence: 99%
“…However the Scott et al (2005) To be considered Level 5 (''efficacious and specific''), modified alpha-theta training would need to be shown to be superior to sham or bona fide treatment. It has not been demonstrated that the Peniston type alpha-theta feedback is more efficacious than sham treatment (Lowe, 1999;Moore & Trudeau, 1998;Trudeau, 2000Trudeau, , 2005aTrudeau, , 2005b or alternative treatment that involves meditation (Taub & Rosenfeld, 1994).…”
Section: Criteria Overviewmentioning
confidence: 99%
See 3 more Smart Citations